Ayurvedic Interventions for Primary Insomnia in the Elderly: A Systematic Review of Clinical Evidence and Research Gaps - Satyajit Pandurang Kulkarni; Shweta Parwe; Pallavi Satyajit Kulkarni; Shivanand S. Tonde (Global Advances in Integrative Medicine and Health, 2026)
Background Primary insomnia is a prevalent sleep disorder in the elderly, often overlooked in integrative care. Ayurveda defines insomnia as a Vata -dominant condition common in geriatrics. Objective To critically appraise clinical studies on Ayurvedic management of primary insomnia in elderly populations and identify methodological gaps. Methods A systematic review utilized PubMed, DOAJ, DHARA, AYUSH Research Portal, and Google Scholar. Eligible studies included randomized controlled trials and case series, in English, focusing on Ayurvedic treatments for insomnia. Results Eleven studies met inclusion criteria. Interventions comprised Shirodhara, Nasya, Netratarpana , and herbal therapies like Tagara, Jatamansi, Ashwagandha , and polyherbal formulations. Most reported beneficial outcomes, but only two targeted elderly patients. Limitations included small sample sizes, lack of comparators, and absent trial registration. Conclusion Ayurvedic therapies show promise for insomnia, but high-quality trials in elderly populations are scarce. Future research needs to focus on age-specific efficacy, standardized methodologies, and integration with contemporary care.